Probability - Rumsey, Deborah J. 1961- (John Wiley & Sons, Inc., 2025)
Learn how to calculate your chances with easy-to-understand explanations of probability. Probability-the likelihood or chance of an event occurring-is an important branch of mathematics used in business and economics, finance, engineering, physics, and beyond. We see probability at work every day in areas such as weather forecasting, investing, and sports betting. Packed with real-life examples and mathematical problems with thorough explanations, Probability For Dummies helps students, professionals, and the everyday reader learn the basics. Topics include set theory, counting, permutations and combinations, random variables, conditional probability, joint distributions, conditional expectations, and probability modeling. Pass your probability class and play your cards right, with this accessible Dummies guide.
Includes index
Keywords: Probabilities; Probabilités; probability